The Influence of Service Quality and Customer Satisfaction on Purchasing Decisions at PT XYZ - Rina Wahyuni Adetiana (Takaza Innovatix Labs Ltd., 2026)
Retail industry competition demands companies to improve service quality and customer satisfaction to drive purchasing decisions. The decline in PT XYZ's turnover indicates the need for evaluation of both factors. This study aims to analyze the influence of service quality and customer satisfaction on purchasing decisions, both partially and simultaneously. The study uses a quantitative approach with descriptive and verification methods. The study population is all customers of PT XYZ in Bekasi City who have made purchases, while the sample is 100 respondents selected using a purposive sampling technique based on the Lemeshow formula. Data were collected through a Likert-scale questionnaire, observation, and documentation, then analyzed using descriptive statistics, data quality tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination with the help of SPSS. The results show that service quality has a positive and significant effect on purchasing decisions (β = 0.350; p < 0.001), customer satisfaction also has a positive and significant effect (β = 0.196; p = 0.002), and both variables simultaneously have a significant effect with a coefficient of determination of 65.3%. In conclusion, improving service quality and customer satisfaction are important factors in improving customer purchasing decisions at PT XYZ